"Sport has always been first for me" but "all my free time is spent doing homework": Dual career styles in late adolescence. (November 2017) - Ryba, Tatiana V.; Stambulova, Natalia B.; Selänne, Harri; Aunola, Kaisa; Nurmi, Jari-Erik
Abstract: Objectives: In adolescence, personally meaningful autobiographical memories begin to integrate into cultural narrative structures to form a life story. We examined how and to what extent adolescent Finnish athletes narrate and integrate significant life events in sport and education into their identities and future narratives in order to delineate the different styles of athletes' career construction. Design: Longitudinal qualitative study. Method: Ten female and eight male, elite junior athletes, aged 15–16 at baseline, participated in individual conversational interviews. The resulting interview data were analyzed using narrative analysis. Results: Thirteen of 18 adolescent athletes drew primarily on the performance narrative plot to construct their life story and five of 18 athletes could not project into the future beyond their athletic selves. We identified three styles of athletes' career construction. Employing musical terminology as a metaphor, the contrapuntal style entwines sport and education as harmonically related life-themes; monophonic style draws on a prominent athletic life-theme; and dissonant style is underpinned by discord of sport and education. We did not detect direct associations between narrative types (performance, discovery and relational) and career construction styles. We show the dominant style development within an exemplary story. Conclusion: Exploration of the future and possible selves are critical for developing meaningful (dis)continuity of a dual career pathway from adolescence to adulthood. We conclude that dual career discourse is gaining traction in directing young athletes' future thinking; however, a broader repertoire of exemplary success stories which allow athletes to imagine achieving excellence in diverse ways would enable them to channel action. Highlights: Through narrative methodology we delineated three styles of athletes' dual career construction. Contrapuntal style entwines sport and education as harmonically related life-themes. Monophonic style draws on a prominent athletic life-theme. Dissonant style is underpinned by discord of sport and education. There is no direct correspondence between narrative types and career construction styles.